Insulin like Growth Factor-1 as a Marker of Nutritional Status and Health - Mallika Manral and SomNath Singh (Al Ameen Medical College, 2011)
Insulin like growth factor-1 (IGF-1) is a peptide hormone that is secreted from liver and is known to mediate many somatotrophic changes. Since IGF-1 has a wide range of metabolic effects, it becomes important to study its relationship with nutrition and health. It seems to be responsive and selective biomarker of energy status due to its rapid response to depletion and repletion.